2022
DOI: 10.3390/rs14071606
|View full text |Cite
|
Sign up to set email alerts
|

Soil Salinity Detection and Mapping in an Environment under Water Stress between 1984 and 2018 (Case of the Largest Oasis in Africa-Morocco)

Abstract: Water stress is one of the factors controlling agricultural land salinization and is also a major problem worldwide. According to FAO and the most recent estimates, it already affects more than 400 million hectares. The Tafilalet plain in Southeastern Morocco suffers from soil salinization. In this regard, the GIS tools and remote sensing were used in the processing of 19 satellite images acquired from Landsat 4-5, (Landsat 7), (Landsat 8), and (Sentinel 2) sensors. The most used indices in the literature were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This state of degradation was also reported in the context of an increasing salinity trend in groundwater in the Tunisian oasis [6] and in an increase in soil salinity area and a degree in all land-use types in the desert-oasis ecotone. In a current study on the Tafilalet area, Rafik et al [53] conducted a spatial-temporal analysis of soil salinity and demonstrated a highly variable and negative association with the standardized precipitation anomaly index. The arid nature of the climate of these areas is represented by temperatures (0-48 • C), irregular annual precipitations (50-150 mm), and hot-dry winds frequently violent (40-50 km/h) favor a very high average evaporation (3358 mm/year) [54].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This state of degradation was also reported in the context of an increasing salinity trend in groundwater in the Tunisian oasis [6] and in an increase in soil salinity area and a degree in all land-use types in the desert-oasis ecotone. In a current study on the Tafilalet area, Rafik et al [53] conducted a spatial-temporal analysis of soil salinity and demonstrated a highly variable and negative association with the standardized precipitation anomaly index. The arid nature of the climate of these areas is represented by temperatures (0-48 • C), irregular annual precipitations (50-150 mm), and hot-dry winds frequently violent (40-50 km/h) favor a very high average evaporation (3358 mm/year) [54].…”
Section: Discussionmentioning
confidence: 86%
“…This serious advancement of the desertified area was accompanied by a considerable reduction of cultivated areas in the study period, principally, in the Tafilalet plain. This can be explained by the less developed class of soil in this area due to the climatic factor, wind, water erosion, and lack of vegetation cover [53].…”
Section: Discussionmentioning
confidence: 96%
“…Land degradation and particularly soil erosion is severely affecting ecosystems, societies and livelihoods globally (Batunacun et al, 2019; Rafik et al, 2022; Reed et al, 2011). The loss of reservoir storage capacity owing to soil erosion is a crucial problem, mainly in semi‐arid and arid counties where water reservoirs play a key role to meet the increasing water needs (Caputo & Carcione, 2013; Ochoa et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the groundwater level is strongly correlated with vegetation. The over-exploitation of groundwater causes a decline in the water table, leading to an accumulation of soil salts and toxins, especially in drought years, in areas of high agricultural activity and increased water stress [15][16][17][18][19][20][21][22]. In China, the relationship between vegetation and groundwater burial depth, as well as the water table, water quality, and soil, has been studied in the Tarim River [23], Hei River [24], Shiyang River Basin [25,26], Sanguang River [27], Inner Mongolia Loop [28], Loess Plateau [29], Hulunbeier in Inner Mongolia [30], Ejina [31], and Gurbantunggut Desert [32,33].…”
Section: Introductionmentioning
confidence: 99%